Uganda : Technical Assistance Report-Report on Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding compilation and dissemination of government finance statistics in accordance with the guidelines of Government Finance Statistics Manual 2001/14. The IMF mission, in collaboration with the Uganda Bureau of Statistics, the Bank of Uganda, and the Ministry of Finance, Planning, and Economic Development, produced a new institutional table that can be further reviewed, adopted, and used as a standard for the entire government of Uganda in the production of statistics. The IMF mission recommends that the government of Uganda continue to disseminate government finance statistics to the IMF and the East African Community and start disseminating a broader range of public sector debt statistics through the World Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet